Synthesis of Novel Benzothiazole-Piperazine Derivatives and Their Biological Evaluation as Acetylcholinesterase Inhibitors and Cytotoxic Agents - Gurdal, Enise E.; Turgutalp, Bengisu; Gulcan, Hayrettin Ozan; Ercetin, Tugba; Sahin, Mustafa Fethi; Durmaz, Irem; Atalay, Rengul Cetin; Nguyen, Quoc Dat; Sippl, Wolfgang; Yarim, Mine (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Objective and Method: A new series of benzothiazole-piperazine derivatives was synthesized and a complete chemical characterization of the novel compounds was provided. In vitro cytotoxic activities were screened against colorectal (HCT-116), breast (MCF-7) and hepatocellular (Huh7) cancer cell lines by Sulforhodamine B assay. Result and Discussion: All compounds showed cytotoxic activity against hepatocellular (Huh7) and breast (MCF-7) cancer cell lines. Dihalo substituted benzylpiperazine derivatives (2a, 2e) had the highest cytotoxic activities in all the tested cell lines. In addition, acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory activities of synthesized compounds were investigated by in vitro Ellman's method. Compound 2j led to moderate and selective inhibition against AChE. Docking study was utilized to understand the binding mode of compound 2j in comparision with donepezil on AChE. The other tested compounds showed weak or no inhibition against AChE as promising anticancer agents.
Keywords: Ellman' s method